Anti-inflammatory Constituents from Caulis Trachelospermi - Song, Hongzhi; Tan, Jinni; Ma, Ruijing; Kennelly, Edward J; Tan, Qingang (Planta Medica, 2021)
Caulis Trachelospermi, the stems with leaves of Trachelospermum jasminoides, is a well-known herbal drug of the Apocynaceae family recorded in the Chinese pharmacopeia and used for the treatment of inflammation-related diseases by ethnic minorities of China. The mechanism of anti-inflammatory activity and responsible constituents of T. jasminoides have not been well elucidated in previous studies. Preliminary investigation showed that both the water and the ethyl ester extracts of T. jasminoides exhibited potent inhibitory activity on nitric oxide (NO) production using lipopolysaccharide (LPS)-stimulated murine macrophages. Phytochemical investigation on these extracts afforded 23 compounds, including three new compounds (1 –3) identified on the basis of spectroscopic and mass spectrometric data. Anti-inflammatory bioassay showed that compounds 17, 18, 22, and 23 inhibited significantly the production of NO in a concentration-dependent manner. Further studies indicated that compound 23 inhibited significantly TNF-α and IL-6 produced by LPS-stimulated RAW 264.7 cells with good selectivity, as well as protein expression of iNOS in RAW 264.7 cells. These chemical constituents may contribute to the anti-inflammatory potential of T. jasminoides.
Keywords: Trachelospermum jasminoides; Apocynaceae; triterpenoid glycosides; NO production; tumor necrosis factor-α; interleukin-6